How to teach quantitative subjects at universities of economics in a comprehensible and pleasant way? - Gaspars-Wieloch, Helena (Jak uczyć ilościowych przedmiotów na uczelniach ekonomicznych w zrozumiały i przyjemny sposób?, 2010)
Nowadays in Poland: the level of pupils‘ and students‘ mathematical skills is constantly decreasing, students refer very seldom to manuals, because they are not able to understand their content, lecturers working at universities are not obliged to have a suitable pedagogical experience, the number of hours designed for mathematical subjects at univer-sities of economics is smaller than it was in the previous decades, university authorities just recommend reducing requirements towards students in order not to loose too many of them at the end of the academic year [...]
Didactics of Mathematics, 2010, Nr 7 (11), s. 33-48
Keywords: colleges economical; effective and fun teaching; teaching quantitative subjects; teaching tips for teachers